Individual Psychology Counseling Approach to Increase Student Self-Acceptance - Farhan Farhan (Journal of Counseling, Education and Society, 2020)
The research is motivated by the author's desire to know how the students' self-acceptance / acceptance of a problem they are facing. The author uses an individualized psychological counseling approach, which feels suitable to the characteristics of the respondent in order to see his self-acceptance, which is needed in life. This research is a qualitative research with a case study approach. The study was conducted at one of the High Schools in the City of Padang. The subjects in this study were one student. Taking the subject of this study using purposive sampling method. This study uses data collection techniques with interviews and observations. The technique guarantees the validity of the data carried out by building close relationships with subjects and informants naturally and continually making observations. Data analysis technique is done by data reduction, data display and conclusion drawing and verification. The results of the study revealed that the conditions of self-acceptance of students in the case are as follows: (1) Students have good confidence in their capacity to cope with the environment, and the environment is good (2) Students consider themselves to be different from others, (3) Students consider themselves reasonable and have expectations that others will accept it, (4) Students can be said to be confident, not ashamed or self-aware, as evidenced by the achievements achieved (5) Students can be responsible for each behavior, but also doubt for the future (6) stand alone, this problem lacked opinion students proved that sometimes affected by social pressures from the community / school environment (7) students can receive objective criticism and praise, (8) students are able to accept strengths and weaknesses possessed, (9) Students do not deny all the feelings that arise. But sometimes it can change the mood to negative. So, it can be concluded that students have good self-acceptance.